DEVELOPMENT OF A CISCO PACKET TRACER-BASED FIREWALL CONFIGURATION LEARNING VIDEO FOR VOCATIONAL HIGH SCHOOL STUDENTS - Fauzan, Mh Fikran; Purwanti, Yuniar; Suprihadi, Dudi (STKIP Citra Bakti, 2026)
Network Security learning in vocational high schools is often constrained by the limited availability of physical firewall devices and the dominance of lecture-based teaching methods, which make it difficult for students to understand abstract configuration concepts. This study aims to develop an instructional video on firewall configuration using Cisco Packet Tracer as a learning medium for the Network Security subject in Vocational High Schools. The development process employed the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects involved 25 eleventh-grade students of Computer and Network Engineering and two expert validators, namely a material expert and a media expert. Data collection instruments included validation sheets and student response questionnaires, while data analysis was conducted descriptively using quantitative methods with a Likert scale. The validation results indicated that the instructional video obtained a feasibility score of 86.7% (Very Feasible) from the material expert and 83.3% (Very Feasible) from the media expert. Meanwhile, the students’ responses showed an average score of 89.6% (Very Feasible). The instructional video is therefore considered highly feasible and has the potential to facilitate students’ understanding of firewall configuration concepts in an engaging and interactive manner. Thus, this media is appropriate to be implemented in practice-based learning to support student learning in the Network Security subject.